Risk management of COVID-19 by universities in China - Chuanyi Wang; Zhe Cheng; Xiao-Guang Yue; Michael McAleer (Journal of Risk and Financial Management, 2020)
The rapid spread of new coronaviruses throughout China and the world in 2019-2020 has had a great impact on China's economic and social development. As the backbone of Chinese society, Chinese universities have made significant contributions to emergency risk management. Such contributions have been made primarily in the following areas: alumni resource collection, medical rescue and emergency management, mental health maintenance, control of staff mobility, and innovation in online education models. Through the support of these methods, Chinese universities have played a positive role in the prevention and control of the epidemic situation. However, they also face the problems of alumni's economic development difficulties, the risk of deadly infection to medical rescue teams and health workers, infection of teachers and students, and the unsatisfactory application of information technology in resolving the crisis. In response to these risks and emergency problems, we propose some corresponding solutions for public dissemination, including issues related to medical security, emergency research, professional assistance, positive communication, and hierarchical information-based teaching.
Keywords: 330; Chinese universities; COVID-19; Information technology; online education; public safety; risk management; Wuhan